Improving the Management of the Crown's Exposure to Risk - Timothy Irwin; Oscar Parkyn (New Zealand Government, The Treasury, 2009)
The paper discusses the management of the New Zealand Crown's exposure to financial risk. It argues that the Crown's aggregate exposure to risk can be effectively managed only centrally, and that, despite the difficulties of measuring risk and specifying an appropriate objective, the government should do more to measure, monitor, and control the Crown's aggregate exposure to risk. The paper goes on to present a new model for quantifying the Crown's exposure to risk, which integrates analysis of the government's accounting assets and liabilities with analysis of projected tax revenue and government spending. Among other results, the model suggests that the annual volatility (standard deviation) of the Crown's comprehensive balance sheet is at present approximately 30 billion.
Keywords: G32; H11; 330; Risk management; Crown balance sheet; Wechselkurspolitik; Währungsrisiko; Außenwirtschaftliches Gleichgewicht; Neuseeland